Effect of the Application of Accounting Information Systems Artificial Intelligence Based on Quality Financial Statements with Control System Internal as a variable moderation in Bank 9 Jambi - Ayudia Febrihartini; Yuliusman Yuliusman; Ratih Kusumastuti (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to determine the effect of implementing an artificial intelligence-based Accounting Information System on the Quality of Financial Statements moderated by the Internal Control System. The population used in this study were Bank 9 Jambi employees. Determination of the research sample using the Purposive Sampling method. The data used in this study is primary data. Respondents in this study were 30 respondents by distributing questionnaires using a Likert Scale. The analysis technique used is Partial Least Square (PLS). The result showed that The Artificial Intelligence-Based Accounting Information System has a positive effect on the Quality of Financial Statements and the Internal Control System can moderate the effect of the Artificial Intelligence-Based Accounting Information System on the Quality of Financial Statements.